2021
DOI: 10.21203/rs.3.rs-150068/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chilean Validation of the Operationalized Psychodynamic Diagnosis - Structure Questionnaire (OPD-SQ) for Personality Structure

Abstract: BackgroundThis is the validation of the Operationalized Psychodynamic Diagnosis - Structure Questionnaire (OPD-SQ)MethodsA clinical sample of 399 adults and a nonclinical sample of 50 healthy adults completed measures of depression, attachment, psychiatric symptomatology and distress. Internal consistency and concurrent validity were assessed. Test-retest and Reliable Change Index were also calculated, as the ability of the OPD-SQ to distinguish between the clinical and control subsamples.ResultsHigh internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The mean of all the scales is an indicator of overall personality performance. Reliability studies in Chile have shown that Cronbach’s internal consistency ranged between 0.92 and 0.68 for the full sample, between 0.91 and 0.67 for the clinical sample, and between 0.87 and 0.48 for the healthy control sample ( Lorenzini et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The mean of all the scales is an indicator of overall personality performance. Reliability studies in Chile have shown that Cronbach’s internal consistency ranged between 0.92 and 0.68 for the full sample, between 0.91 and 0.67 for the clinical sample, and between 0.87 and 0.48 for the healthy control sample ( Lorenzini et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%